Early growth and development of morphological defenses in post-hatchling flatbacks (Natator depressus) and green turtles (Chelonia mydas). Issue 6 (1st November 2016) - Salmon, Michael; Wyneken, Jeanette; Hamann, Mark; Whiting, Scott
Abstract: Marine turtles produce hundreds of precocial offspring ("hatchlings") that are virtually defenseless. Many are consumed by predators. Hatchlings improve their survival prospects by migrating to offshore "nursery" areas with lower predator densities and, as they grow, by developing morphological defenses. The flatback turtle ( Natator depressus ), however, remains in the predator-rich coastal waters of Australia. To gain insights into how they survive there, we compared patterns of early growth and morphological development in flatbacks to their closest relative, the green turtle ( Chelonia mydas ), which migrates offshore. We found that morphological structures likely to be used in defense are better developed in juvenile flatbacks than in juvenile green turtles. Those structures probably represent one of a suite of characters that enable young flatbacks to survive in coastal habitats where interactions with predators are likely to be more frequent.